The effectiveness of legal role of village consultative Agency (BPD) in Village development according to UU.No. 6 year 2014 about village (Kahianga Village study) - Laode Muhammad Karim; Deddy Mursanto (Jurnal Hukum Volkgeist, 2020)
The purpose of this research is to know the effectiveness of legal role of the Village consultative Agency (BPD) in the development of the village according to UU.No. 6 year 2014 about village (Kahianga Village study) and to find out the factors that inhibit the role of the Village consultative Agency (BPD) in development in the village Kahianga East Tomia District. The data collection techniques used more on observation, a dandokumentation interview. The conclusion of this research is the effectiveness of legal role of the village consultative body (bpd) Kahianga in the case that legislation does not go as it should, proved in the absence of the rules that are issued, in the meantime in the case of the function budgeting bpd goes well, proved by always involved in the budget discussion meetings that are done with the principle of transparency and supervision function bpd also goes well seen with the active bpd in surveillance of the village's income and expenditure budget and factors that become constraints BPD Kahianga in the development of the village namely the community participation Kahianga Village to the development program is still relatively low, the level of education is relatively low is a BPD inhibitors communicate well and able to analyze the aspirations or what the next community is in coordinate with the village government and the pattern of parallel relations between the BPD and the village head in the village government , it turns out that in the implementation is colored by the practices of working relationships that are less harmonious and leads to the occurrence of conflicts and shows the tendency to dominate the village chief of the BPD.